Probiotic Administration Increases Mandibular Bone Mineral Density on Rats Exposed to Cigarette Smoke Inhalation - Levi,Yara Loyanne de Almeida Silva (2019)
Abstract Smoking is one of the main risk factor for periodontal disease, increasing its prevalence and severity. Probiotics emerged as an alternative for the prevention and treatment of many diseases, since it can modulate the host immune response and modify the modify the microbiome. Therefore, the aim of the present study is to evaluate the effects of probiotic administration on the periodontal tissues in rats exposed to cigarette smoke inhalation (CSI). Forty rats were allocated into the following groups (n=10): group C (control, without CSI and probiotic); group PROB (control+probiotic); group CSI (CSI) and group CSI+PROB (CSI+probiotic). Groups PROB and CSI+PROB received 2g of an association of probiotic microorganisms incorporated into the feed during 6 months. Groups CSI and CSI+PROB were exposed to CSI for 60 min daily. After six months all the animals were euthanized and the hemi-mandibles were collected and processed for microcomputed tomography analyses. Regarding the body weight of the animals, feed consumption was similar among the groups, however, after the second month groups C and PROB showed higher body weight gain when compared to groups CSI and CSI+PROB (p<0.05). Group CSI presented reduced bone mineral density (BMD), whereas group PROB showed the highest values (p=0.01). It can be concluded that administration of probiotics promoted an increase in BMD and, consequently, a protective effect on the mandibular bone structures in rats exposed to inhalation of cigarette smoke.